Academic visit IMD313: expanding knowledge to Sarawak State Records Repository / Saidatul Emyra Tasya Nazri - Nazri, Saidatul Emyra Tasya (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The academic visit by Diploma in Information Management (IM110) students to the Sarawak State Records Repository on June 13, 2024, aims to expose Part 5 students to the processes involved in records management, the technologies used in managing records, and the preservation and conservation of records. This visit involved 22 Semester 5 students from the Diploma in Information Management (IM110), accompanied by Ms. Suhaida Halamy, our lecturer for the subject Foundation of Archives (IMD313). The objectives of the visit were to fulfill the subject requirements, enhance students' theoretical knowledge, and provide them with valuable handson experience in records management at the Sarawak State Records Repository. The journey from UiTM Samarahan Campus to the Sarawak State Records Repository took about 40 minutes. We departed at 1:00 PM and arrived precisely at 1:40 PM. Upon our arrival, all students, including myself, were required to sign the logbook provided outside the entrance. Additionally, we were required to wear visitor passes offered on the table before entering the Sarawak State Records Repository.